Salud mental y sabiduría práctica : un intento de integración y aproximación conceptual (2012)
ABSTRACT: When talking about mental health, usually go to the technical concept that was proposed in 1950 by the World Health Organization (WHO). In this article I will refer initially to the background of this concept, dating back to the Mental Hygiene Movement of the first half of the twentieth century and the second part will show its relationship to a broader sense, the ‘soul health’, understood as practical wisdom.